Effect of crevice gap on crevice corrosion initiation and development of 2205 duplex stainless steel in NaCl solution - Bin Luo; Qian Hu; Jing Liu; Feng Huang (Journal of Materials Research and Technology, 2022)
The crevice geometry has an important influence on the initiation and development of crevice corrosion. The crevice gap size determines the volume of the crevice solution and the cross-sectional area of the material exchange channel between the crevice solution and bulk solution, and it is the dominant factor of the initiation and development mechanism of crevice corrosion. In this paper, the effect of crevice gap size on the crevice corrosion behavior of 2205 duplex stainless steel (DSS) in NaCl solution was investigated by electrochemical method combined with modeling. The quantitative contribution of the volume effect of crevice solution and the diffusion effect of H+ on the crevice corrosion initiation period, as well as the corrosion characteristics and mechanism at initiation and development periods of crevice corrosion, were discussed. Results show that the initiation process of crevice corrosion of 2205 DSS in 3.5 wt% NaCl solution follows the critical crevice solution mechanism. The crevice gap size affects the acidification rate of the crevice solution and the initiation period time of crevice corrosion through the volume effect and the diffusion effect. The influence of diffusion effect on the initiation period time was more significant than volume effect. The corrosion development process is mainly determined by the potential and current density distribution within the crevice, and thus follows the IR drop mechanism (I refers to the current and R refers to the resistance). The crevice gap size is the dominant factor for the development mechanism of crevice corrosion.